Seed production of pasture species in a tropical savanna region of Brazil. 1. Legumes - Andrade, Ronaldo P. de; Thomas, D.; Ferguson, John E. (1983)
The seed yields and limitations to yield for nine pasture legumes in a tropical savanna region were defined in a 3-year field experiment at the Cerrodos Agricultural Research Centre near Brasilia (15°36' S, 47° 42' W). Assessment was based on flowering times, incidence of diseases and pests, yield of pure seed and seed size. Stylosanthes capitata, S. macrocephala, S. hamata, and Zornia latifolia produced annual pure seed yields of 199, 185, 323 and 692 kg ha 1, respectively. The major limitations to seed yield were (a) diseases for Stylosanthes spp. and Zornia latifolia CIAT 728, (b) weeds for S. capitata CIAT 1078, and (c) soil moisture stress for Desmodium ovalifolium CIAT 350, and probably Stylosanthes guianensis CIAT 2243. The flowering time information was used to indicate field photoperiodic responses for six of the legumes studied. Weed infestation and disease problems were considered the major limitations to seed production for these legumes in the Cerrados region.